2015
DOI: 10.1080/10864415.2015.1029358
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Development and Diffusion of Mobile Commerce Technologies in China: A Biographical Study with an Actor-Network Theory Perspective

Abstract: Mobile commerce technologies cater to multiple types of users who use them for various purposes in a dynamic fashion over time. Their development and diffusion therefore involves many actors who participate in changing market configurations. In this study we address this complex sociotechnical setting by investigating the "biography" of mobile text messaging, an instance of mobile commerce technologies, in China. Specifically, we apply an actor-network perspective to understand the development and diffusion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Various applications and services are being developed for mobile phone users, with short message services (SMS) a classical killer application (Drossos et al , 2013; Tseng and Teng, 2016). As smartphones have gained more popularity, mobile instant messaging (MIM) – messaging applications with multimedia capabilities – has been catching up with SMS (Wang et al , 2015). Moreover, 600 million people were using MIM during Q2 2014, an increase of 30 per cent since Q4 2012 (Mander, 2014, according to Global Web Index report, which covers 32 countries and nearly 90 per cent of the global Internet audience).…”
Section: Introductionmentioning
confidence: 99%
“…Various applications and services are being developed for mobile phone users, with short message services (SMS) a classical killer application (Drossos et al , 2013; Tseng and Teng, 2016). As smartphones have gained more popularity, mobile instant messaging (MIM) – messaging applications with multimedia capabilities – has been catching up with SMS (Wang et al , 2015). Moreover, 600 million people were using MIM during Q2 2014, an increase of 30 per cent since Q4 2012 (Mander, 2014, according to Global Web Index report, which covers 32 countries and nearly 90 per cent of the global Internet audience).…”
Section: Introductionmentioning
confidence: 99%
“…The authors identify twenty constructs that influence engagement in check-in behavior and demonstrate that social condition plays the most critical role in motivating people. The second study, by Youwei Wang, Yufei Yuan, Ofir Turel, and Zhiling Tu [30], investigates the "biography" of a common service: mobile text messaging, in China. The authors base their analysis on 1,403 news items that were screened from more than 40,000 news items over sixteen years.…”
Section: Papers In the Special Issuementioning
confidence: 99%
“…For this special issue, three articles [8,13,30] were selected from an initial set of twenty-eight submissions. The articles have undergone several cycles of revision and selection.…”
Section: Papers In the Special Issuementioning
confidence: 99%
“…A actor-network approach-based study on smartphone use revealed a multistage mobile commerce technology diffusion pattern, which can serve as a platform for further study and promotion of the diffusion of multipurpose information and communication services (Wang et al, 2015). The present study applies the actor-network approach to the Internet Village Motoman Project because the use of technology in rural areas where most users live below the poverty line involves complex factors.…”
Section: Tanzaniamentioning
confidence: 99%